THE INFLUENCE OF ORGANIZATIONAL COMMUNICATION ON THE PERFORMANCE OF KELURAHAN EMPLOYEES IN THE WEST BOGOR DISTRICT, BOGOR CITY - Setiana, Ayi; Zenju, Nandang Saefudin; Saleh, M. Yamin (Administratie: Jurnal Administrasi Publik, 2021)
The organization of Government and Regional Development has been regulated in Law No. 32 of 2004 concerning Regional Government, which emphasizes the principle of decentralization in concrete, broad, and responsible forms, starting from planning, implementation, supervision, control, to program implementation evaluation. The performance of village officers in the area of West Bogor District, Bogor City, based on observation results, has not been optimal, and this is suspected to be due to weak organizational communication. The purpose of this research is to analyze the extent of the influence of organizational communication on the performance of village officers in the West Bogor District, Bogor City, and to explore theories and concepts related to organizational communication and employee performance, along with its aspects. Using the Survey Explanatory method, the population in this study consists of villages in the West Bogor District, Bogor City, totalling 16 administrative areas. The research sample was taken using a census sample of 35 employees. The data analysis technique used is Path Analysis. Based on the research results, it is known that simultaneously, the variable of organizational communication empirically has a significant influence on the performance of village officers in the West Bogor District, Bogor City, which is equal to 0.775 or 77.5%.